Etika Produksi Konten Deepfake dalam Promosi Produk Halal: Telaah Fikih Media dan Perlindungan Konsumen Muslim: The Ethics of Deepfake Content Production in Halal Product Promotion: A Study of Islamic Media Jurisprudence and Muslim Consumer Protection - Ihwan Wahid Minu; Nasrullah bin Sapa (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, IndonesiaInstitut Agama Islam STIBA Makassar, Indonesia, 2025)
This study examines the use of deepfake technology in halal product promotion, which poses new ethical challenges within the frameworks of media jurisprudence, Islamic economics, and consumer protection. The aim is to analyze the practice of deepfake content production from the perspective of Islamic ethics and media jurisprudence, assess its impact on Muslim consumer perception, and formulate Sharia-based ethical guidelines grounded in maqāṣid al-sharī‘ah. The research employs a qualitative approach using library research and content analysis methods, drawing data from classical and contemporary literature, the Qur’an, Hadith, and previous studies. The findings reveal that the use of deepfake technology in halal promotion has the potential to create misinformation (tagrīr), violate the principles of honesty (ṣidq) and trustworthiness (amānah), and undermine consumer protection. The study emphasizes the importance of maqāṣid al-sharī‘ah as an ethical standard for validating digital content. The main contribution of this research lies in formulating a Sharia ethical framework for halal digital marketing practices, which can serve as a guideline for producers, academics, and policymakers to maintain the competitiveness of the halal industry without neglecting moral and spiritual responsibility.